2016
DOI: 10.14507/epaa.24.2322
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of High-Stakes Accountability Policies in Teacher Preparation: An Examination of the U.S. Department of Education’s Proposed Regulations

Abstract: Using a sociological framework this article explores the emergence and possible consequences of the 2015 U.S. Department of Education’s proposed federal regulatory policy on teacher education programs and alternative route providers. After describing the key features of the policy, we examine the research literature looking for evidence of the merits of accountability policies in improving teacher education and preparation quality and outcomes. Although there is some research evidence that increased accountabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Poor performance according to these measures could lead to consequences as severe as program closure. The rules spurred considerable opposition (Tatto et al, 2016), and they were eventually rescinded by Congress in the spring of 2017. Even so, this idea has not gone away at the state level.…”
Section: Introductionmentioning
confidence: 99%
“…Poor performance according to these measures could lead to consequences as severe as program closure. The rules spurred considerable opposition (Tatto et al, 2016), and they were eventually rescinded by Congress in the spring of 2017. Even so, this idea has not gone away at the state level.…”
Section: Introductionmentioning
confidence: 99%
“…The openness of the charge and the comprehensive structure of the PRC supported agency. By working in partnership, teacher educators, regulators, and policymakers created a pathway for inclusive policymaking that allowed for multiple voices to be heard through a chaotic but genuine feedback process, which is an aspirational aim of the field (see Tatto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In an age of accountability, it is critical to define and estimate the effects of various educational factors on student learning in a manner that allows stakeholders to explore potential reasons for what is observed and to enhance program quality and fidelity (Tatto et al 2016). When evaluating teacher training programs, Goldhaber (2013) suggested that such estimates should provide opportunities to answer more nuanced questions about the programs themselves and what features "quality" programs possess.…”
Section: Estimating Program Effects: Existing and Proposed Methodsmentioning
confidence: 99%